Physiological plasticity of beech (Fagus sylvatica L.) under contrasting light conditions - Mészáros, Ilona (Acta Biologica Szegediensis, 2002)
In this work pigment composition and chlorophyll fluorescence characteristics were studied in seedlings of Fagus sylvatica regenerating in contrasting light environments of forest understory, forest edge and deforested area. The results have shown that the survival of beech seedlings under high light conditions in the forest edge and deforested area, as well as their acclimation to excess light require effective functional plasticity of the photosynthetic apparatus and protective mechanisms. Physiological acclimation of beech seedlings to high light involves significantly the carotenoids both in the short-term through the reversible conversion of violaxanthin to zeaxanthin and in the long-term through the increase of total carotenoid content and the size of xanthophyll cyc e pool.